Answer :

To find: p (1)

Put x = 1 in the given polynomial

p (1) = (1)^{4} – 2 × (1)^{2} – 1

= 1 – 2 – 1

p (1) = -2

To find: p (0)

Put x = 0 in the given polynomial

p (0) = 0 – 0 – 1

p (0) = -1

To find: p (-2)

Put x = -2 in the given polynomial

p (-2) = (-2)^{4} – 2 × (-2)^{2} – 1

= 16 – 2 × 4 – 1

= 16 -8 -1

= 7

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

Write the correctMHB - Math Part-I

Write the degree MHB - Math Part-I

Write the followiMHB - Math Part-I

Subtract the secoMHB - Math Part-I

Write the followiMHB - Math Part-I

Write the index fMHB - Math Part-I

Add the followingMHB - Math Part-I

Write the correctMHB - Math Part-I

Write the correctMHB - Math Part-I

Write the correctMHB - Math Part-I